Biochemical parameter and feto-maternal outcome in preeclampsia: a hospital based observational study - Nagar, Teena; Nagar, Rajendra P.; Gupta, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preeclampsia is one of the maternal diseases that cause detrimental effects on to the maternal, fetal, and neonatal health. The objective of the present study was to analyse maternal, perinatal outcome and investigation parameter in preeclampsia. Methods: This is an observational study and total of 90 consecutive patients were enrolled who has blood pressure ≥ 140/90 mmHg after 20 weeks of gestation with proteinuria (1+ by dipstick). Results: Among enrolled patients, 52 (58%) were in age group of 25-35 year and 51 (57%) were primigravida. Mean systolic and diastolic blood pressure of patients was 148±3.8 mm of Hg and 95±1.4 mm of Hg respectively. Most common presenting symptom was labor pain in 65 (72%) patients followed by edema in 61 (68%) patients. Most common complication was CNS symptom including seizure (Eclampsia) in 13 (15%) patients followed by vaginal bleeding (including abruption) in 12 (13%) patients. Mean hemoglobin level was 9.12±0.9 gm/dl. Mean urea and creatinine values were 34±4.6 mg/dl and 1.5±1.1 mg/dl respectively. Out of total 90 patients, 18 (20%) had elevated liver enzymes. Most common neonatal outcome was low birth weight 63 (70%) and 40 (44%) were preterm. APGAR score was less than 7 in 11 (12%) patients and more than 7 in 79 (88%) patients. Five (5.5%) newborn were still born. Conclusions: Preeclampsia is associated with multiple maternal and neonatal complications. Hence, there is a need for regular antenatal checkup to detect early and strengthening of neonatal intensive care units.